2009
DOI: 10.1007/s11096-009-9344-6
|View full text |Cite
|
Sign up to set email alerts
|

Information sources used by women in Finland who use hormonal contraceptives

Abstract: The importance of health care professionals as sources of information concerning hormonal contraceptives has increased. However, role of pharmacists as information source was surprisingly small. Women who use hormonal contraceptives need more information from professional sources to alleviate possible fears associated with use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
3
3
0
Order By: Relevance
“…Previous studies have mostly applied single cross-sectional study designs 38–46. We found only one study that compared results from 2 years, covering a 7-year period 47. The consistent findings from the previous studies are that physicians, pharmacists and package leaflets are the most common sources of MI regardless of the research method, the study year, the country and the research population 21–47.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Previous studies have mostly applied single cross-sectional study designs 38–46. We found only one study that compared results from 2 years, covering a 7-year period 47. The consistent findings from the previous studies are that physicians, pharmacists and package leaflets are the most common sources of MI regardless of the research method, the study year, the country and the research population 21–47.…”
Section: Introductionsupporting
confidence: 75%
“…We found only one study that compared results from 2 years, covering a 7-year period 47. The consistent findings from the previous studies are that physicians, pharmacists and package leaflets are the most common sources of MI regardless of the research method, the study year, the country and the research population 21–47. Consumers usually sought MI from only one or two information sources 28 34 39 43 44.…”
Section: Introductionsupporting
confidence: 72%
“…Reminders could not be sent because customers were recruited anonymously. A similar method has been successfully used in a few earlier studies targeted at Finnish pharmacy customers [7,30,31].…”
Section: Methodsmentioning
confidence: 99%
“…The study sample was also large, involving pharmacy customers across mainland Finland. The response rate of 40% is typical for this kind of method where it was impossible to send reminders [7,29,30]. There are no comparable statistics on Finnish pharmacy customers' characteristics.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…19 Thus, Miia Tiihonen found that women prefer health care professionals when it comes to getting information about the benefits of contraceptives and the adverse effects. 25 Women informed by community health agents are more likely to use contraception. To Lee, those informed by community health agents also have a higher contraceptive use.…”
mentioning
confidence: 99%